Pelvic Stress Fracture among Naval Cadets in Bangladesh - Quader, Mohammad Abdul; Farhana, Irin (Community Based Medical Journal, 2024)
Stress fractures are often found in military recruits. Most involved bones are tibia, metatarsals, calcaneus and fibula. Pelvic stress fracture especially at pubic ramus is relatively rare; however, it is found more in females in comparison to its male counterpart. A prospective study was carried out to investigate demographic features of pelvic stress fractures among the Naval cadets in Bangladesh. A total of 18 patients with pelvic stress fractures reported at the Department of Orthopedics of Bangladesh Naval Ship (BNS) Patenga Hospital at Chattogram, Bangladesh, between January 2021 and December 2022. Naval trainee officers both male and female undergo physical and military training during their courses. Most of the cadets reported with pain in their groin. Routine investigation was done. Plain radiograph of pelvis revealed fracture lines sometimes periosteal elevation and sclerosis. The mean age of the patients was 18.94 years (ranging between 18 and 20 years). Out of 18 patients, 17 were female and 1 was male. All the cadets were treated conservatively. Post trauma pain developed in 3(16.67%) cases, while the rest 15(83.33%) recovered completely. CBMJ 2024 January: vol. 13 no. 01 P: 66-70